The Effects of a Secondary Science Training Program on the 1 Procedures, and Processes of Science. - Cody, John T.; Pizzini, Edward L. (Science Education)
The article focuses on the effects of the Secondary Science Training Program (SSTP) initiated by the National Science Foundation designed to foster increased relevance in academic studies, enhance student understanding, encourage student initiative, and accelerate the growth of scientific talents in the U.S. The basic purposes of the SSTP includes: (1) evoking direct interaction between scientists and high school students; and (2) having unique experiences emphasizing the methods and procedures of science. The results of the study indicates that the research program that lacked the lecture and directed laboratory component was not effective. The implications of the study for science educators interested in increasing the understanding of methods, procedures, and the processes of science emphasize the inclusion of a blend of teaching strategies. Finally, the growth in both the methods and procedures as well as the processes of science was maximized by blending instructional techniques.